1989
DOI: 10.1002/j.1537-2197.1989.tb11283.x
|View full text |Cite
|
Sign up to set email alerts
|

Thermomorphogenesis in Lilium Longiflorum

Abstract: Stem elongation and leaf orientation in Lilium longiflorum Thunb. were influenced more by the difference (DIF) between day temperature (DT) and night temperature (NT) than absolute DT or NT from 14 to 30 C. Plant height and internode length increased 129 and 382%, respectively, as DIF (DT‐NT) increased from –16 to 16 C as compared to only 15 and 58% when either DT or NT was increased from 14 to 30 C, respectively. Leaf orientation, defined as the angle between a line perpendicular to the stem and the line from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
91
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 111 publications
(106 citation statements)
references
References 18 publications
13
91
2
Order By: Relevance
“…These studies showed that stem elongation in Campanula was influenced more by the difference between day and night temperature than by average daily temperature or absolute day or night temperature between 12 and 24~ Similar responses have been reported for other species as well, Fuchsia • hybridia (Tangerfis 1979), Lilium longiflorum (Erwin et al 1989), and Dianthus chinensis (Moe 1983).…”
supporting
confidence: 49%
See 1 more Smart Citation
“…These studies showed that stem elongation in Campanula was influenced more by the difference between day and night temperature than by average daily temperature or absolute day or night temperature between 12 and 24~ Similar responses have been reported for other species as well, Fuchsia • hybridia (Tangerfis 1979), Lilium longiflorum (Erwin et al 1989), and Dianthus chinensis (Moe 1983).…”
supporting
confidence: 49%
“…The systematic error can be calculated by comparing the response of GA97 with the response of D2-GA ~ in the mass spectrometer. (Moe 1990) and some other species as well (Erwin et al 1989) suggest an involvement of GA in the thermoperiodic regulation of elongation growth. In addition to effects on the levels of bioactive GAs, changes in tissue sensitivity to GA can be influenced by environmental factors (Nick and Furuya 1993, Pinthus et al 1989, Reid and Ross 1991.…”
Section: Discussionmentioning
confidence: 99%
“…These growth responses were similar under negative DIF conditions, probably because the negative DIF value was −4.5°C under SD and −9°C under LD. Exogenously applied GAs can eliminate the negative DIF inhibition of stem elongation (Erwin 1991, Ihlebekk et al 1995, Moe 1990, Myster et al 1997, Tangerås 1979, Zieslin and Tsujita 1988, shown here with GA 1 , GA 4 , and GA 9 . In relative values, the effect of applying e.g.…”
Section: Figmentioning
confidence: 99%
“…Recently, it has been shown that internode elongation is closely related to DT − NT (DIF) in many plant species (Erwin 1991, Erwin et al 1989, Moe 1990, Moe and Heins 1990). For strong growing cultivars of the short day (SD) plant Begonia x hiemalis negative (DT < NT) or zero DIF (DT ‫ס‬ NT) results in compact plants of good quality (Myster and Moe 1995, Myster et al 1997, Willumsen et al 1995.…”
mentioning
confidence: 99%
“…In general, plants grow tall with long internodes when the DT is higher than the NT, whereas a short phenotype with short internodes is developed under a DT lower than the NT. These thermoperiodic responses have been utilized for control of plant height in commercial plant production in climatecontrolled conditions (Bakken and Flønes 1995, Erwin et al 1989, Moe 1994. The two opposite temperature combinations have been referred to as temperature regimes with a positive (positive DIF, high DT/low NT) and negative difference between DT and NT (negative DIF, low DT/high NT), respectively.…”
mentioning
confidence: 99%